1988
DOI: 10.7863/jum.1988.7.1.21
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of the clavicle in the newborn. An ultrasound diagnosis.

Abstract: Forty-one cases of clavicle fracture in newborn babies were examined by both radiographic and ultrasonic methods. No substantial difference has been found between these two modalities. It is suggested that ultra· sound should be the procedure of choice in the diag· C lavicle fracture is the most common fracture in the full-term newborn after vaginal delivery. 1 .2 The clinical signs are typical and include local findings and diminished movement of the ipsilateral arm. Clavicle fracture can be diagnosed by ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 1 publication
0
13
0
1
Order By: Relevance
“…The value of ultrasonography as a diagnostic tool for the detection of "bone" fractures (eg, in congenital hip dislocation, fractures of the radial or clavicular bone, or fractures of the ribs or skull) has been proven in various studies. [5][6][7][8] To our knowledge, only 4 studies [9][10][11][12] have dealt with the diagnosis of nasal fractures by ultrasound imaging. Danter et al an ultrasound device to investigate nasal fractures in 18 patients.…”
mentioning
confidence: 99%
“…The value of ultrasonography as a diagnostic tool for the detection of "bone" fractures (eg, in congenital hip dislocation, fractures of the radial or clavicular bone, or fractures of the ribs or skull) has been proven in various studies. [5][6][7][8] To our knowledge, only 4 studies [9][10][11][12] have dealt with the diagnosis of nasal fractures by ultrasound imaging. Danter et al an ultrasound device to investigate nasal fractures in 18 patients.…”
mentioning
confidence: 99%
“…13 We have shown that ultrasound examination is an excellent method for confirming a suspected fracture of the clavicle in the neonate. One of the first studies of the use of ultrasound for the diagnosis of such fractures in the neonate was published by Katz et al, 14 but the method is still not widely used. The sonographic criteria for a clavicular fracture with interruption of the hyperechogenic zone of the bone, steps, axial deviation and visible periosteal lesions are similar to those in other fractures (Table II).…”
Section: Discussionmentioning
confidence: 99%
“…Williamson et al [27] reported using modestly high frequency (6-10 MHz) probes to detect pediatric forearm fractures, while Chen et al reported 97% sensitivity and 100% specificity for similar pediatric fractures [25]. Finally, Katz et al [28] reported that there is no significant difference between the detection of newborn pediatric fractures with either US or radiography.…”
Section: Reported Experiencementioning
confidence: 99%